25th International Conference On Ground Control In Mining - Geology, Ground Control, And Mine Planning At Bowie Resources, Paonia, Co - Collin Stewart; Greg Hunt; Christopher Mark (The National Institute for Occupational Safety and Health (NIOSH))
Bowie Resources maintains one of the most pro-active ground control programs in the U.S. mining industry today. Its guiding philosophy is that everyone in the organization, from the miners at the face all the way through the top management, are involved in ground control. Some of the unique elements of the Bowie ground control program include: • Roof bolt operators log the stratigraphy of test holes in nearly every cut. These “lith-graphs” are used by section foremen to determine the need for additional roof support, and they are entered into the geologic data base for use in geologic modeling and mapping. • Underground core drilling is conducted to obtain data for CMRR and stability maps. • Weekly “Quality” meetings, involving mine management and technical staff, are held to ensure that ground control information is integrated into production operations. The paper will describe the program in detail, discussing the involvement of roof bolters, section foremen, surveyors, technical staff, and production managers. It will also show how the program has contributed to the mine planning process. Case histories of successful ground control interventions will be discussed.